Temperature Compensation of a Thermal Flow Sensor by Using Temperature Compensation Network - Noraznafulsima, Khamshah; Abdalla, Ahmed N.; Badaruddin, Muhammad (2009)

(untitled)
There has been a growing demand for flow-temperature sensors for industrial, automotive, domestic and medical applications, a quick response and low power consumption. The error of flow temperature measurement is one of the most important problems of sensors. In this paper, the Temperature Compensation Network has been developed for temperature compensation of a Thermal flow Sensor in the Wheatstone bridge circuit. The method allows for a broad range of temperature compensation from -20 to +70oC. The proposed scheme leads to an error reduction of approximately 96.45% from temperature uncompensated value.